Expanded Carrier Screening in Chinese Population – A Survey on Views and Acceptance of Pregnant and Non-Pregnant Women - Cheng, Hiu Yee Heidi; Wong, Grace Ching Yin; Chan, Yuen-Kwong Kelvin; Lee, Chin Peng; Tang, Mary Hoi Yin; Ng, Ernest Hung-Yu; Kan, Anita Sik-Yau (Frontiers in Genetics, 2020)
Objective: Recessive genetic diseases impose physical and psychological impacts to both newborns and parents who may not be aware of being carriers. Expanded carrier screening (ECS) allows screening for multiple genetic conditions at the same time. Whether or not such non-targeted pan-ethnic approach of genetic carrier screening should replace the conventional targeted approach remains controversial. There is limited data on view and acceptance of ECS in general population, as well as the optimal timing of offering ECS to women. This study assesses views and acceptance of ECS in both pregnant women and non-pregnant women seeking fertility counseling or checkup, and their reasons for accepting or declining ECS. Materials and methods: This is a questionnaire survey with ECS information in the form of pamphlets distributed from December 2016 to end of 2018. Women were recruited from the antenatal clinics and the assisted reproductive unit at Department of Obstetrics & Gynaecology, Queen Mary Hospital and the prepregnancy counselling clinic at the Family Planning Association of Hong Kong. Results: A total of 923 women were recruited; 623 pregnant women and 300 non-pregnant women. There were significantly more non-pregnant women accepting ECS compared to pregnant women (70.7% vs 61.2%). Eight-hundred and sixty-eight (94%) women perceived ECS as at least as effective as or superior to traditional targeted screening. Significantly more pregnant women have heard about ECS compared with non-pregnant women (42.4% vs 32.3%, p=0.0197). Majority of women showed lack of understanding about ECS despite reading pamphlets that were given to them prior to filling in the questionnaires. Cost of ECS was a major reason for declining ECS, 28% (n=256). Significantly more pregnant women worried about anxiety caused by ECS compared with the non-pregnant group (21.1% vs 7.4%, p = 0.0006). Conclusion: Our study demonstrates that expanded carrier screening was perceived as a better screening by most women. Prepregnancy ECS maybe a better approach than ECS during pregnancy, as it allows more reproductive options and may cause less anxiety. Nevertheless, implementation of universal pan-ethnic ECS will need more patient education, ways to reduce anxiety and consensus on optimal timing in offering ECS.